ANALISIS KEPERCAYAAN DIRI ANAK USIA DINI DALAM KAJIAN STUDI SOSIAL - Aini, Alvin Nur; Setiadi, Anggun Chandrasari; Mahdavika, Annisa; Nabilah, Sendy Ufairoh (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2021)
Experts reveal that the socio-emotional development of children aims to find out how children are responsible for themselves and others in the social sphere. The environment around children has a role in influencing children's emotional development and can be a source of problems for children if they get inappropriate behavior, such as being selfish, not confident, and so on. Therefore, teachers or parents must create a peaceful environment so that there are no problems in children's emotions. This study aims to describe how children's self-confidence is seen from social studies studies. There are several solutions that parents can take in this case: (1) Spending quality time with their children; (2) Provide opportunities for children to mingle with the surrounding environment under constant supervision, (3) Enough in giving praise, flattery, gifts so that children are not accustomed to doing something in return, (4) Always teach and instill in children the meaning of the proverb "there is a sky above". Langit", (5) Not prioritizing physical punishment (pinch, hitting, etc.) when a child makes a mistake, but warns with words first, and (6) Provides opportunities for children to show or do things they like.